Penerapan Prinsip-Prinsip Good Corporate Governance dalam Pengelolaan Wakaf Tunai pada Badan Wakaf Uang Tunai MUI Yogyakarta - Triwibowo, Ananto (Tapis: Jurnal Penelitian Ilmiah, 2020)
As a public institution that has a mandate to manage the waqf cash fund, the waqf agency is required to be capable of managing the cash waqf fund and implementing the principles of Good Corporate Governance (GCG) as a form of responsibility to public The impact of the implementation of GCG itself, in addition to improve the level of public trust, will increase the amount of fund accepted by the waqf agency. This research aims to describe the management of cash waqf and to analyze the implementation of Good Corporate Governance (GCG) principles respectively done and in BWU/T MUI DIY in the management of cash waqf. This is a qualitative-descriptive research using a case study approach aimed to describe the reality of the cash waqf management and the implementation of GCG principles in BWU/T MUI DIY. The results were then analyzed or measured using the theories relevant with the issues concerned. In addition, this research used SWOT analysis to observe the strengths, weaknesses, opportunities and challenges in managing the cash waqf faced by the BWU/T MUI DIY. Based on the results of the research, it can be found that in the management of the cash waqf done by BWUT MUI DIY overall has been implemented in accordance with the existing laws, either from legislation, regulation of religion minister, and regulation issued by BWI. Meanwhile for the implementation of GCG principles in the management of cash waqf done by BWUT MUI DIY recently has not been done maximally. Of five basic principles of GCG including transparency, accountability, responsibility, independence and fairness, in fact there are only two principles conducted entirely that is the principle of independence and fairness. On the other hand, the principles of transparency, accountability, and responsibility have not been applied entirely.